Объединенный клеточный метод умножения матриц - Елфимова, Л.Д. (Кибернетика и системный анализ, 2013)
Запропоновано об’єднаний клітинний метод множення матриць, який являє собою гібрид трьох методів: рекурсивних методів Штрассена, Лейдермана та швидкого клітинного методу множення матриць. Взаємодія трьох методів забезпечує найвищий порівняно з відомими методами відсоток мінімізації (37 %) мультиплікативної, адитивної та загальної складності клітинних аналогів відомих алгоритмів множення матриць. Оцінку обчислювальної складності об’єднаного методу наведено на прикладі отримання клітинного аналога традиційного алгоритму множення матриць. A unified cellular method of matrix multiplication is proposed that is a hybrid of three methods, namely, Strassen’s and Laderman’s recursive methods and a fast cellular method for matrix multiplication. The interaction of these three methods provides the highest (in comparison with well-known methods) percentage (equal to 37%) of minimizing the multiplicative, additive, and overall complexities of cellular analogues of well-known matrix multiplication algorithms. The estimation of the computational complexity of the unified method is illustrated by the example of a model of obtaining a cellular analogue of the traditional matrix multiplication algorithm.